2022
DOI: 10.48550/arxiv.2202.06416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State-of-the-Art Review of Design of Experiments for Physics-Informed Deep Learning

Abstract: This paper presents a comprehensive review of the design of experiments used in the surrogate models. In particular, this study demonstrates the necessity of the design of experiment schemes for the Physics-Informed Neural Network (PINN), which belongs to the supervised learning class. Many complex partial differential equations (PDEs) do not have any analytical solution; only numerical methods are used to solve the equations, which is computationally expensive. In recent decades, PINN has gained popularity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…All statistics indicate that RANG-m achieves the best performance. Consistent with the previous result [20], the Hammersley sampling performs best among the four non-resampling methods. In this example, we can also see that RANG-m is more stable than RANG.…”
Section: Allen-cahn Equationsupporting
confidence: 88%
See 3 more Smart Citations
“…All statistics indicate that RANG-m achieves the best performance. Consistent with the previous result [20], the Hammersley sampling performs best among the four non-resampling methods. In this example, we can also see that RANG-m is more stable than RANG.…”
Section: Allen-cahn Equationsupporting
confidence: 88%
“…IDRLnet [40] provides jittered grid sampling. The authors of [20] explored the construction of point sets from the perspective of experimental design, compared various methods, and found that Hammersley sampling works well. In the PINN library SimNet [41], Halton pseudo-random sequence is provided as an alternative algorithm for generating low-discrepancy points.…”
Section: Hammersley Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-discrepancy sequences usually perform better than uniformly distributed random numbers in many applications such as numerical integration; hence, a comprehensive comparison of these methods for PINNs is required. However, very few comparisons [34,35] have been performed. In this study, we…”
Section: Related Work and Our Contributionsmentioning
confidence: 99%